MATLAB Simulink Analysis of Switch Matrix for Optimal Solar PV Array Efficiency - Lawrence, Ting; Then, Yi Lung; Abadi, Chanik; Hazrul, Mohamad Basri; Hadi Nabipour, Afrouzi (Semarak Ilmu Sdn Bhd, 2023)
This study addresses the challenge of partial shading in solar photovoltaic (PV) systems, which limits power output in conventional configurations. To enhance efficiency, this research explores both static and dynamic reconfiguration strategies, integrating a switch matrix to adapt to diverse shading conditions. The static approach employs Sudoku puzzle pattern for matrix structuring, while the dynamic approach utilizes a controllable switching matrix within electrical array reconfiguration (EAR) to respond to environmental variability. The methodology involves simulating a 3 × 3 PV array in MATLAB Simulink to assess power optimization across varying shading scenarios. Findings reveal that incorporating the switch matrix significantly improves power output, offering valuable insights for scalable PV systems under partial shading. This work emphasizes the switch matrix's critical role in enhancing both flexibility and performance in PV arrays.